2019
DOI: 10.1155/2019/1429548
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Liriope platyphylla Extract Attenuates Dry Eye Syndrome Induced by Particulate Matter

Abstract: Particulate matter (PM) is a type of air pollutant that poses a risk to human health. In the ocular system, PM causes or aggravates dry eye syndrome (DES) by damaging the corneal and conjunctival epithelia. Liriope platyphylla has been used traditionally as an expectorant, antitussive agent, and tonic in Korea. However, the effects of Liriope platyphylla extract (LPE) on PM-induced ocular damage have not been elucidated. In this study, we evaluated the in vivo protective effect of LPE against PM-induced DES in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Each AVP scan was composed of five segments: orbital optic nerve, intracanalicular optic nerve, intracranial optic nerve, optic chiasm and optic tract. 12 ( Figure 1) Treatment outcomes, including time from initial ocular symptoms (pain and/or visual loss) to IVMP administration, and BCVA at recovery were also analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Each AVP scan was composed of five segments: orbital optic nerve, intracanalicular optic nerve, intracranial optic nerve, optic chiasm and optic tract. 12 ( Figure 1) Treatment outcomes, including time from initial ocular symptoms (pain and/or visual loss) to IVMP administration, and BCVA at recovery were also analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous reports demonstrated that women are disproportionately affected by DED, are diagnosed at a younger age, and experience more severe symptoms compared with men [69,70]. Similar to the human studies, several animal studies suggested female sex is a risk factor for DED [5,71,72]. McClellan et al [71] reported that female C57BL/6 mice developed greater corneal barrier disruption than age-matched male mice did, although other features of DED such as low goblet cell density and LG infiltration were similar in both sexes.…”
Section: Discussionmentioning
confidence: 81%
“…McClellan et al [ 71 ] reported that female C57BL/6 mice developed greater corneal barrier disruption than age-matched male mice did, although other features of DED such as low goblet cell density and LG infiltration were similar in both sexes. Recently, Song et al [ 72 ] used six-week-old female SD rats to assess the effect of natural products on a PM 2.5 -induced DED model. Yang et al [ 5 ] also used 6–8-week-old female C57BL/6 mice to evaluated the harmful effect of PM 2.5 on the eye.…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that L. platyphylla can protect against ocular damage induced by particulate matter exposure. Topical L. platyphylla extract applied in rats with DED induced by urban particulate matter increased tear volume, decreased corneal epithelial cell injury and apoptosis, restored the corneal mucin-4 layer, and maintained the conjunctival goblet cell density [ 37 ].…”
Section: Urrent Research On Traditional Chinese Medicine In the Treatment Of Dry Eye Diseasementioning
confidence: 99%